Aproximación del costo de la implementación de la ruta de promoción y mantenimiento en salud según resolución 3280 en una IPS de Ibagué, 2023 - Torres Cárdenas, Freydell Javier (Universidad Antonio Nariño, 2024)
Cost study of the health promotion and maintenance route in patients in charge of an IPS in the city of Ibague, Tolima calculated for the year 2023, whose objective was to make the financial and economic determination as an input for decision-making in terms of financial planning of an IPS of first and second level services. The study was conducted by a microeconomic, quantitative, transversal study of descriptive scope as a cost analysis concerning the technical note of the IPS and the EPS, with the measurement of the variables of average event cost and frequency of us